Validation of SYBR green I based closed tube loop mediated isothermal amplification (LAMP) assay and simplified direct-blood-lysis (DBL)-LAMP assay for diagnosis of visceral leishmaniasis (VL). - Keerti Kaumudee Dixit; Sandeep Verma; Om Prakash Singh; Dharmendra Singh; Akhil Pratap Singh; Ratan Gupta; Narendra Singh Negi; Pradeep Das; Shyam Sundar; Ruchi Singh; Poonam Salotra (Public Library of Science (PLoS), 2018)
Background The World Health Organization has targeted elimination of visceral leishmaniasis (VL) in the Indian subcontinent (ISC) by 2020. Despite distinctive decline seen in the number of VL cases in ISC, there is still a quest for development of a diagnostic test which has the utility for detection of active infection and relapse cases and as a test of cure. The present study validated the sensitivity and specificity of SYBR Green I based closed tube LAMP assay reported by us for diagnosis of VL. Methodology The validation study was carried out at two endemic sites in India, located at Rajendra Memorial Research Institute of Medical Sciences (RMRIMS), Patna and Institute of Medical Sciences (IMS), Banaras Hindu University (BHU), Varanasi. Standard operating protocols were provided at the two sites for applying LAMP assay on confirmed VL cases. The diagnostic accuracy of LAMP assay was evaluated by Receiver operator curve (ROC) analysis. Furthermore, a simplified LAMP assay based on direct blood lysis, DBL-LAMP, was developed and verified for its diagnostic accuracy. Principal findings A total of 267 eligible participants were included in the study which comprised of 179 VL cases and 88 controls. Sensitivity and specificity of the LAMP assay were 98.32% (95% C.I- 95.2-99.7%) and 96.59% (95% C.I.-90.4-99.3%), respectively. ROC curve analysis depicted no significant difference between area under curve (AUCROC) for LAMP assay and rK39 RDT, indicative of LAMP as an excellent diagnostic test. DBL-LAMP assay, performed on 67 VL and 100 control samples, yielded a sensitivity of 93.05% (95% C.I- 84.75-97%) and specificity of 100% (95% C.I.- 96.30-100%). Conclusions/significance The validated closed tube LAMP for diagnosis of VL will provide impetus to the ongoing VL elimination programme in ISC. The assay based on direct blood lysis promotes its scope for application in field settings by further reducing time and cost.